DxR Clinician - Congenital Defect Case (Out of Print) - Hurley Myers (Association of American Medical Colleges, 2006)
Abstract Health care professionals face the difficult task of determining the clinical reasoning skills of individual students. While observing and mentoring students during preclinical patient encounters and clinical clerkships can provide considerable insight into the clinical reasoning procedure, they do not provide any means of quantifying specific skills. This congenital defect case, on the other hand, has the ability to monitor each action of a student during a simulated patient encounter and to provide feedback about the level of clinical reasoning demonstrated. The student asks questions, conducts a physical exam, orders lab tests, makes a diagnosis, and recommends a management plan. Following these activities, the student receives online feedback via a comparison of his/her investigation process with that of the case author. This and other DxR Clinician cases have been reviewed extensively by faculty and institutions worldwide and shown to be an effective way to allow users to conduct a clinical investigation by giving access to a complete database of virtual patient information.